Magnetic phase transitions in the system La1-xBixMnO3+l: Дефекты в кристаллах - Troyanchuk, I. O.; Mantytskaja, O. S.; Szymczak, H.; Shvedun, M. Yu. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
The crystal structure and magnetic properties of the La1-xBixMnO3+l system( ; 0 £ x1£l £ 0.08 ) are studied as functions of the oxygen and bismuth contents. In oxidized samples La1-xBixMnO3+l a phase transition from a ferromagnetic state (rhombohedric phase) to a state of the spin glass type (quasitetragonal phase) is observed with increase of the bismuthconcentration. The reduced samples La1-xBixMnO3 are weak ferromagnets down to x £ 0.6 andthen transform into a ferromagnetic state. It is supposed that the Bi3+ ions stabilize thedx²-y² orbitals in the nearest Mn3+ ions whereas the dz² orbitals of the La3+ ions are stabilized. The orbitally disordered phases and dx²-y² - orbitally ordered phases are ferromagnetic, the dz² - orbitally ordered phases show antiferromagnetic ordering, and the state of the orbital glass type corresponds to a state of the spin glass type.